Acceleration of Random Testing for Software - Shengfeng Wu; Yue Wu; Shiyi Xu (2013 IEEE 19th Pacific Rim International Symposium on Dependable Computing, 2013)
Random testing has been widely used in both software and hardware testing areas for years, which is applied as black box testing in software testing. This paper takes advantage of the common features of hardware and software random testing, applying the new concept of the maximum distance among test patterns called Quasi Perfect Maximum Distance Test Sequence (QPMDTS) into software. It is an effective extension from the hardware point of view to fit software testing by using some suitable transformations and improvements so that the random testing procedure can be greatly accelerated. A number of experiments on 39 mutant versions of benchmark program and empirical experiments on four subject programs from numerical recipes have been completed and the favorable results have shown the real effectiveness of the proposed method compared with other random testing techniques. It concludes that the proposed method of test cases generation for software can not only bring higher fault coverage but also a lower test cost compared with the conventional software random testing.